2021
DOI: 10.2166/wst.2021.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the selection of common adsorption substrates for extensive green roofs (EGRs)

Abstract: Adsorption substrate in the substrate layer of an extensive green roof (EGR) is one of the most important factors affecting rainwater retention and pollution interception capacity. However, the contact time between runoff and adsorption substrate is extremely short in actual rainfall, and adsorption substrate cannot show fully rainwater retention and pollution interception capacity. So, selection of adsorption substrate based on its physical properties and theoretical adsorption capacity is unreliable. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Substrate adsorption is a fast-acting process 38 and vermiculite has high cation exchange and NH 4 + –N adsorption capacity. 22 Thus, the NH 4 + –N interception performance of SL was not significantly affected by rainfall depth even in rainstorm events. However, the addition of additives instead amplified the negative impact of rainfall depth on NH 4 + –N interception of the substrate layer.…”
Section: Discussionmentioning
confidence: 80%
“…Substrate adsorption is a fast-acting process 38 and vermiculite has high cation exchange and NH 4 + –N adsorption capacity. 22 Thus, the NH 4 + –N interception performance of SL was not significantly affected by rainfall depth even in rainstorm events. However, the addition of additives instead amplified the negative impact of rainfall depth on NH 4 + –N interception of the substrate layer.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the total CLQ of TN in the PVG outflow was lower than that of PV, indicating that the combination of vermiculite and green zeolite configures in the substrate layer with direct mixing or layered configuration had better nitrogen interception capacity than single vermiculite. Xu et al (2021) found that single vermiculite, as the substrate layer, has better rainfall runoff interception efficiency than single green zeolite. Therefore, the selection of a mixed adsorption substrates instead of a single adsorption substrate in the substrate layer can effectively improve the EGR ability to intercept nitrogen in rainfall runoff.…”
Section: Resultsmentioning
confidence: 97%
“…The total CLQ of TN in the PVGL outflow during the entire simulated rainfall process was the lowest (199.397 mg). Furthermore, the total CLQ of TN in the PVG outflow was lower than that of PV, indicating that the combination of vermiculite and green zeolite configures in the substrate layer with direct mixing or layered configuration had better nitrogen interception capacity than single vermiculite Xu et al (2021). found that single vermiculite, as the substrate layer, has better rainfall runoff interception efficiency than single green zeolite.…”
mentioning
confidence: 88%
“…24 Vermiculite is a silicate mineral with strong ion exchange capacity and has been proven in numerous works in literature to be an excellent adsorption substrate. 12,30…”
Section: Methodsmentioning
confidence: 99%
“…24 Vermiculite is a silicate mineral with strong ion exchange capacity and has been proven in numerous works in literature to be an excellent adsorption substrate. 12,30 PAC and bentonite were used as the modifiers in this study. Both PAC and bentonite have a certain degree of cohesiveness in the wet state, which is conducive to the formation of AS in the substrate layer.…”
Section: Experimental Devicementioning
confidence: 99%